THE LOCA OPTIMIZATION OF FLIGHT PLAN DELIVERY IN KOTABARU UNIT LPPNPI PERUM - Syahnan Syah Ammar, Muhammad; Fatmawati, Fatmawati (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
This final project describes the constraints faced by the author regarding the LOCA between the ATS RO unit and Wings Abadi Airlines regarding the delivery of the flight plan at Perum LPPNPI Kotabaru Unit. The absence of submitting flight plans using the Web Based Flight plan method resulted in a less than optimal process for submitting flight plans at the ATS RO unit, which resulted in flight delays. The research method used by the author is descriptive qualitative, data collection methods are in the form of observations and interviews regarding obstacles in sending flight plans which are still manual and according to researchers it is necessary to conduct a LOCA review to deal with them. The results of this study indicate that the LOCA between the ATS RO unit and the Airlines Operator at Perum LPPNPI Kotabaru Unit is not optimal, especially in the delivery of flight plans, so a review is needed by adding points containing regulations in the form of coordination steps related to this matter. problem into an existing LOCA. with the aim that flight plan delivery can be more optimal so that flight plan delivery is more efficient. and the results of this study the researcher reviewed the contents of the location between the ats reporting office and wings abardi airlines by adding points about flight plan delays with the aim that flight plan delivery could be more optimal